2008
DOI: 10.2967/jnumed.108.055764
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Signaling Enhances Sodium Iodide Symporter Function and Efficacy of Radioiodide Therapy in Nonthyroidal Cancer Cells

Abstract: Although the success of sodium/iodide symporter (NIS) genebased cancer therapy is critically dependent on the level of radioiodide accumulation attained, recent evidence indicates that successful therapy relies not solely on NIS amount but also crucially on its functional activity. In this study, we investigated the role of kinase-linked signaling on the regulation of NIS function in cancer cells. Methods: T47D human breast cancer and PC-12 rat pheochromocytoma cells were transduced with the human NIS genes vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Treatment with epidermal growth factor increased iodide uptake in NIS -transfected T47D human breast cancer cells, as well as PC12 rat pheochromocytoma cells. This effect was abolished by PD98059 (Jung et al, 2008), a MEK-1 inhibitor, indicating a role of the MEK-ERK signaling cascade in the NIS translocation.…”
Section: Posttranslational Regulation Of Nismentioning
confidence: 98%
See 1 more Smart Citation
“…Treatment with epidermal growth factor increased iodide uptake in NIS -transfected T47D human breast cancer cells, as well as PC12 rat pheochromocytoma cells. This effect was abolished by PD98059 (Jung et al, 2008), a MEK-1 inhibitor, indicating a role of the MEK-ERK signaling cascade in the NIS translocation.…”
Section: Posttranslational Regulation Of Nismentioning
confidence: 98%
“…The NIS translocation to the cell surface membrane is enhanced by EGF (epidermal growth factor) receptor stimulation in NIS -introduced non-thyroidal cancer cells (Jung et al, 2008). Treatment with epidermal growth factor increased iodide uptake in NIS -transfected T47D human breast cancer cells, as well as PC12 rat pheochromocytoma cells.…”
Section: Posttranslational Regulation Of Nismentioning
confidence: 99%
“…It may take advantage of the enormous progress obtained in thyroid cancer field of research in the elucidation of the molecular mechanism that controls thyrocyte differentiation and, in particular, NIS expression. For example, inhibitors of signal transduction pathways, as PI3K/AKT inhibitors and MEK/ERK inhibitors, or HDAC inhibitors, have demonstrated the ability to enhance the functional NIS expression in some thyroid cancer, as well as non-thyroid cancer cells [85,117,118] and, very recently, a clinical pilot study has actually demonstrated the effectiveness of the MEK inhibitor selumetinib to increase radioiodide uptake in a number of patients with advanced thyroid cancer [114]. …”
Section: Review and Conclusionmentioning
confidence: 99%
“…Besides increasing the intracellular levels of cAMP, TSH can also act by activating other intracellular pathways, such as ERK-MEK and p38MAPK [46]. However, the actual importance of these pathways as modulators of the expression and activity of NIS is still controversial [46,47,48]. NIS expression and function can also be modulated by pathways activated by insulin and IGF-1 [49,50].…”
Section: Sodium-iodide Symportermentioning
confidence: 99%